Not so simple: The threats to leadership sustainability. (July 2016) - Bottery, Mike
This article begins by examining the possible meanings of 'sustainability', and argues that most meanings are prescriptive rather than descriptive in nature: they tend, either overtly or covertly, to recommend the particular end-states that writers desire. The article then looks at the threats to leadership sustainability, suggesting that a lack of sustainability is not only caused by excessive volume of work and lack of preparation for the role, but also by how different stakeholders view the role. Greater sustainability, it is proposed, comes from recognizing the 'wicked' rather than the 'tame' nature of the role, and of the need to apply solutions which reflect the 'wicked' nature of many leadership challenges. Finally, links are made between leadership sustainability and the sustainability of larger social, economic and environmental systems, suggesting that they have many similar causes and many similar remedies.